PURCHASING DECISION: DO YOU NEED SERVICE QUALITY, PRODUCT QUALITY AND WORD OF MOUTH? - Yano, Midori Aiko; Ikhsani, Mastur Mujib; Rahayu, Tri Septin Puji; Kharismasyah, Alfato Yusnar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to analyze the effect of service quality, product quality and word of mouth on purchasing decisions. The population is consumers at Purwokerto Cosmetic Warehouse. The sample of this study amounted to 100 respondents with the roscoe quota technique. The data analysis technique used is Structural Equation Modeling (SEM) Part Least Square (PLS). The results of this study show that service quality has a positive effect on purchasing decisions, product quality has a positive effect on purchasing decisions, word of mouth has a positive effect on purchasing decisions. Keywords: Purchasing decision, quality of service, product quality, word of mouth